THE EFFECTIVENESS OF THE SELF-MANAGEMENT OF HEALTH MODEL OF ELDERLY PERSONS IN NORTHERN REGION AFTER THE PANDEMIC OF COVID-19 SITUATION - Hamera, Chaturong; Arunchote, Kritsana; Kongurai, Umaporn; Wongwachara-umpon, Thanigaporn (Academic Journal of Thailand National Sports University, 2025)
This research was carried out using for quasi-experimental method. The objective was to study the effectiveness of the self-health management model the elderly in the upper northern region after the COVID-19 outbreak 62 elderly subjects aged 60 years and older. Using G*power version 3.1.2, were obtained by purposive sampling. The tools used in this research were: 1) self-health management models for the elderly and 2) self-assessment of the health management for the elderly. The mean differences in self-health management for the elderly in the experimental and control groups using independent t-test, and the mean differences in self-health management for the elderly in the pre-test and post-test using dependent t-test were compared. The results showed that the experimental group had higher average score of self-health management than the control group, significantly at the 0.05 level. The post-test of self-health management score had higher than the pre-test of self-health management score, significantly at the 0.05 level. In apparently in conclusion, the self-health management model was useful for the elderly in the upper northern region